Comparisons between flour qualities produced by three different mills: buhler, quadrumat, and industry mills - Abeer S. Alhendi; Tamadher H. Ahmad; Wasan S. Albayati; Balsam Q. Almukhtar; Zahraa K. Ali; Nuhoodh K. Al-Hayani (International Journal of Food Studies)
Three types of mills (Buhler, Quadrumat, and industry mill) have been used to determine the effect of mill type on the quality of the produced flour. Quadrumat and Buhler mills are usually used to produce flour at a laboratory level. Flour quality has been determined physically, chemically, and rheologically. Results showed that the particle size of flour produced by Buhler mill (FPB) was finer (mostly less than 132 μm) than other produced flour, while flour produced by Quadrumat mill (FPQ) had 8% particle size bigger than 50gg, which is more than Iraqi accepted limit (5%). The moisture content of FPQ exceeded the moisture content limit (14%). While, all flour produced by industry mills (FPI) was within the Iraqi standard in term of particle sizes and moisture content. Gluten content of FPB was higher than other produced flours; however, most increments were not significantly different. The results also showed that using different mills has no clear effect on the gluten index and alpha-amylase activity. Farinogram and extensogram results showed that FPQ was stronger than other produced flour followed by FPI. In conclusion, the quality of FPQ was closer to the quality of FPI, however, Quadrumat mill needs to be adjusted to produce flour with finer particle sizes and lower moisture content. The Buhler mill, on the other hand, needs to be adjusted to produce flour with bigger particle size. Both laboratory mills (Quadrumat and Buhler) need to be adjusted to produce flour that expresses FPI correctly.